2015
DOI: 10.15403/jgld.2014.1121.244.csd
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Infection in Hospitalized Cirrhotic Patients with Hepatic Encephalopathy

Abstract: Hospitalized cirrhotics with HE are at risk for developing CDI, and clinicians treating such patients should be aware of this infection as rapid detection and prompt treatment may improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…In our cohort, the incidence of CDI cirrhotic patients was 24.8 cases per 10,000 person-year, lower than the incidence reported in a cohort of cirrhotic patients with HE [ 18 ]. Previous studies demonstrated that in the general population treated with antibiotics, 5% of the patients developed CDI [ 19 ]; in our cohort 6.7% developed CDI during norfloxacin secondary SBP prophylaxis.…”
Section: Discussioncontrasting
confidence: 75%
“…In our cohort, the incidence of CDI cirrhotic patients was 24.8 cases per 10,000 person-year, lower than the incidence reported in a cohort of cirrhotic patients with HE [ 18 ]. Previous studies demonstrated that in the general population treated with antibiotics, 5% of the patients developed CDI [ 19 ]; in our cohort 6.7% developed CDI during norfloxacin secondary SBP prophylaxis.…”
Section: Discussioncontrasting
confidence: 75%
“…First, HE was found to be associated with a decreased risk of CDI despite being associated with an increased risk of bacterial infections. This is rarely commented on in the literature, with another study coming to the opposite conclusion . The effect of medications commonly used to treat HE offers potential explanations.…”
Section: Discussionmentioning
confidence: 96%
“…Some local data also provide epidemiological figures for CDI in cirrhosis. In a study from a tertiary hospital in Romania [ 35 ], CDI occurred in 7.3% of 231 patients with cirrhosis coexisting with hepatic encephalopathy (HE) (mainly stage 2 or 3) between 2012 and 2014, with an overall CDI incidence of 57.2 cases per 10,000 patient days. In a small prospective study conducted in Romania in 2015, among 200 Child-Pugh B and C patients hospitalized for decompensation, 9% developed CDI during their hospitalization [ 36 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Age >65 years, multiple hospitalizations, inpatient stays >20 days, hypoproteinemia, Clostridioides difficile colonization (CDC), HE, antibiotic, and proton pump inhibitors (PPIs) use were found to be associated with the development of CDI in a study conducted to identify risk factors for CDI in patients with cirrhosis [ 45 ]. Furthermore, many studies have also reported risk factors for CDI development [ 22 , 23 , 30 , 32 , 35 , 37 , 39 , 46 49 ] although heterogeneity exists between studies. The risk factors concluded from these studies are largely in line with the previous research and can be broadly classified into several categories, namely medications (PPIs, antibiotics, etc.…”
Section: Risk Factorsmentioning
confidence: 99%